Association between life's essential 8 and periodontitis: a population-based study - XingJin Chen; JiangLing Sun; ChongWen Zeng; FuQian Jin; Shu Ma; Jukun Song; Zhu Chen (BMC, 2024)
Abstract Background The American Heart Association has developed a novel cardiovascular health indicator called Life's Essential 8 (LE8). However, no one has reported using LE8 to assess periodontitis. This study aimed to investigate the association between LE8 and periodontitis in American adults. Methods Data from the National Health and Nutrition Examination Survey (NHANES) from 2009 to 2014 were used for this investigation. LE8 was the independent variable, and it is divided into three grades: high, moderate, and low. Periodontitis was the dependent variable, and the classification of periodontitis was based on the criteria of Eke in 2012. Multivariable logistic regression models were used to explore the relationship between LE8 and periodontitis. Results A total of 9,039 participants with an average age of 52.16 ± 14.21 years were enrolled in this study, of whom 48.29% were male and 51.71% were female. The mean and standard deviation of LE8 was 66.29 ± 14.57, and the prevalence of periodontitis was 50.48% overall. The LE8 score and periodontitis in the fully adjusted logistic regression model showed a negative correlation (OR = 0.98; 95% CI, 0.98-0.99, p < 0.001). This result persisted when Life's Essential 8 was categorized into low, moderate, and high groups. Compared with those in the lowest group, those in the highest LE8 group had a 47% decreased risk of periodontitis (OR = 0.53; 95% CI, 0.46-0.66, P < 0.001). Conclusions This cross-sectional investigation revealed a negative relationship between the LE8 score and the likelihood of periodontitis.